1983
DOI: 10.1254/jjp.33.1263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prostaglandins on mucosal blood flow and aspirin-induced damage in the canine stomach.

Abstract: Abstract-This study deals with the action in anesthetized dogs of prostaglandin E2 and F20 given into the celiac artery and the femoral vein on gastric mucosal blood flow and on gastric mucosal damage induced by aspirin. In the non-stimulated stomach , infusion of prostaglandin E2 or F2 into the celiac artery resulted in a marked increase in mucosal blood flow and a sustained decrease, respectively. In contrast, an infusion of pro staglandin E2 into the femoral vein produced a decrease in mucosal blood flow , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Even though the lack of increase in resting GBF may be a secondary response related to the fall of SBP, the result coincides with previous observations (22,23) that PGE2 and 16,16-dimethyl PGE2 did not increase resting GBF.…”
Section: Discussionsupporting
confidence: 91%
“…Even though the lack of increase in resting GBF may be a secondary response related to the fall of SBP, the result coincides with previous observations (22,23) that PGE2 and 16,16-dimethyl PGE2 did not increase resting GBF.…”
Section: Discussionsupporting
confidence: 91%
“…This technique has been shown to provide unreliable values during changes in acid output (Holm-Rutili & Berglindh 1986) or when acid output is low (Archibald et al 1975). Other investigators (Inatomi & Maki 1983), however, have suggested that the inconsistent results reported earlier were not due to the differences in the method of measurement but to the differences in the route of administration.…”
Section: E T H O D Smentioning
confidence: 98%
“…Earlier reports on the influence of exogenous PGEs on GMBF are conflicting (Jacobson 1970, Main & Whittle 1973, Cheung & Lowrey 1978a, Cheung et al 1978b, Robert 1981, Gerber & Nies 1982, Inatomi & Maki 1983. It has been suggested (Gerber & Nies 1982) that discrepancies in the reported effects of PGEs on GMBF arose from the use of the AP clearance technique.…”
Section: E T H O D Smentioning
confidence: 99%
See 1 more Smart Citation